Training program effectiveness of service initiators: measuring perception of female employees of bank using logistic approach - Azam, S. M. Ferdous; Haque, A. K. M. Ahasanul; Sarwar, Abdullah; Anwar , Naila (An online journal of management, 2014)
Banking sector is one of the vital parts of the financial sector that has significant influence in the economy of Bangladesh. Due to lack of skilled manpower, banks often fail to generate quality services to the customers which can be an obstacle for the growth of this sector. Therefore, training programs are conducted for the employees in order to improve their skills for providing quality service activities. This study aims to assess the female employee’s perception of increased services after participating in the training program. Female employees were chosen due to its dominance in providing few banking services. Samples were collected from female employees working in different banks using the simple random technique. For investigating how different variables influence the dichotomous dependent variable Logit model has been implemented. The ultimate outcomes of the study have demonstrated that effective training program is influenced by few factors that have an impact on the performance of the female employees.